Duality: wall art in craft appreciation / Eqbal Naqib Elmi-Rizal - Elmi-Rizal, Eqbal Naqib (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
"Duality" is an exploration of wall art design that seeks to merge the distinct preferences associated with masculinity and femininity, utilizing traditional materials to create a harmonious fusion. Through a meticulous analysis of gender-specific tastes. "Duality" aims to challenge conventional stereotypes and present a visual narrative that reflects a shared appreciation for the richness of both masculine and feminine sensibilities. "Duality" invites viewers to appreciate the synergy between seemingly opposing elements, fostering a deeper understanding of the interconnected nature of design, gender expression, and artistic creativity. Through this blend of traditional materials and innovative design, "Duality" contributes to a more inclusive and forward-thinking approach to wall art, celebrating the beauty that emerges when traditional craftsmanship meets contemporary ingenuity.